2010
DOI: 10.1088/0953-8984/22/22/223201
|View full text |Cite
|
Sign up to set email alerts
|

Charge distribution near bulk oxygen vacancies in cerium oxides

Abstract: Understanding the electronic charge distribution around oxygen vacancies in transition metal and rare earth oxides is a scientific challenge of considerable technological importance. We show how significant information about the charge distribution around vacancies in cerium oxide can be gained from a study of high resolution crystal structures of higher order oxides which exhibit ordering of oxygen vacancies. Specifically, we consider the implications of a bond valence sum analysis of Ce₇O₁₂ and Ce₁₁O₂₀. To i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 131 publications
4
65
0
Order By: Relevance
“…The two electrons are typically modelled as being localised at NN sites to the vacancy, 50,[67][68][69][70] although recent studies have reported them to be located at next-nearest neighbour (NNN) sites. 71,72 To assess the application of the occupation matrix control methodology to this kind of defective f-element system, the SOD code 58 was again used to identify all symmetry inequivalent combinations of arranging the two Ce(III) ions within the O-deficient cell. Due to the high symmetry of the fluorite lattice, the number of possible arrangements was only 33, full details of which are provided in the ESI.…”
Section: Ceomentioning
confidence: 99%
“…The two electrons are typically modelled as being localised at NN sites to the vacancy, 50,[67][68][69][70] although recent studies have reported them to be located at next-nearest neighbour (NNN) sites. 71,72 To assess the application of the occupation matrix control methodology to this kind of defective f-element system, the SOD code 58 was again used to identify all symmetry inequivalent combinations of arranging the two Ce(III) ions within the O-deficient cell. Due to the high symmetry of the fluorite lattice, the number of possible arrangements was only 33, full details of which are provided in the ESI.…”
Section: Ceomentioning
confidence: 99%
“…[15,16] In fact, ceria normally contains many defects, that is, oxygen vacancies, which enable it to rapidly give up or take up oxygen atoms in a reversible manner. When an oxygen atom is released according to Equation (1), two of the four neighboring Ce 4+ atoms get reduced to their +3 oxidation state in order to equilibrate the charge, as depicted in Figure 1.…”
Section: Protective Effects Of Ceria Materialsmentioning
confidence: 99%
“…When an oxygen atom is released according to Equation (1), two of the four neighboring Ce 4+ atoms get reduced to their +3 oxidation state in order to equilibrate the charge, as depicted in Figure 1. [16,17] Figure 1. Simplified schematic representation of the charge redistribution in CeO 2 upon the occurrence of an oxygen vacancy.…”
Section: Protective Effects Of Ceria Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, some metal oxide nanoparticles present this property, as is the case of cerium oxide nanoparticles. Cerium oxide exhibit catalytic properties since they present a reversibility of the oxidation states Ce þ3 and Ce þ4 that leads to oxygen vacancies [81]. Lord et al [82] investigated the antioxidant properties of cerium oxide nanoparticles in U-937 derived macrophages (PMA-differentiated) exposing the cells for up to 72 h to the nanoparticle.…”
Section: Macrophage Activation By Metal-oxide Nanomaterialsmentioning
confidence: 99%